(untitled) (International journal of artificial intelligence, 2026)
This article examines the significance of the chromatographic method in medical research, its main types, and areas of application. Specifically, the role of chromatographic methods in pharmaceuticals, clinical diagnostics, and forensic medicine is analyzed. The importance of modern chromatographic technologies in increasing accuracy and efficiency is also highlighted. The article discusses the molecular-level identification capabilities of methods such as HPLC, GC, and LC, as well as the principles of "Green Chromatography".